2017
DOI: 10.3390/ijms18071537
|View full text |Cite
|
Sign up to set email alerts
|

BRD9 Inhibition, Alone or in Combination with Cytostatic Compounds as a Therapeutic Approach in Rhabdoid Tumors

Abstract: Rhabdoid tumors (RT) are malignant neoplasms of early childhood. Despite intensive therapy, survival is poor and new treatment approaches are required. The only recurrent mutations in these tumors affect SMARCB1 and less commonly SMARCA4, both subunits of the chromatin remodeling complex SWItch/Sucrose Non-Fermentable (SWI/SNF). Loss of these two core subunits alters the function of the SWI/SNF complex, resulting in tumor development. We hypothesized that inhibition of aberrant SWI/SNF function by selective bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 52 publications
(71 reference statements)
3
40
1
Order By: Relevance
“…While the loss of SMARCB1 compromises both BAF and PBAF, it does not affect GBAF that lacks this subunit (Alpsoy and Dykhuizen 2018;Gatchalian et al 2018;Mashtalir et al 2018;Michel et al 2018). Therefore, it is of interest that chemical probes that target the GBAF subunit BRD9 inhibit proliferation of RT cell lines (Krämer et al 2017;Michel et al 2018). Collectively, these observations suggest that RTs might be especially vulnerable to combined targeting of BRD9 and EZH2.…”
Section: Smarcb1 In Rhabdoid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the loss of SMARCB1 compromises both BAF and PBAF, it does not affect GBAF that lacks this subunit (Alpsoy and Dykhuizen 2018;Gatchalian et al 2018;Mashtalir et al 2018;Michel et al 2018). Therefore, it is of interest that chemical probes that target the GBAF subunit BRD9 inhibit proliferation of RT cell lines (Krämer et al 2017;Michel et al 2018). Collectively, these observations suggest that RTs might be especially vulnerable to combined targeting of BRD9 and EZH2.…”
Section: Smarcb1 In Rhabdoid Tumorsmentioning
confidence: 99%
“…For example, SMARCB1 deficient cells require residual SWI/SNF function, because concomitant loss of SMARCB1 and SMARCA4 blocks tumor development (Wang et al 2009). Moreover, SMARCB1 mutant RT cells also depend on BRD9 function (Krämer et al 2017;Michel et al 2018). ARID1A mutant cancer cells often require the function of its paralog ARID1B (Helming et al 2014;Kelso et al 2017;McDonald et al 2017).…”
Section: Therapeutic Opportunities: Restoring or Tipping The Chromatimentioning
confidence: 99%
“…Although no statistically significant association between BRD9 expression and tumour stage or survival was found in our study, BRD9 importance must not be overlooked, since the available literature states that expression alterations in other important genes such as CDKN2A also do not correlate with patient prognosis in melanoma [35][36][37]44]; this could be the case of BRD9. Moreover, BRD9 inhibition has been shown to result in decreased cell proliferation, G1-arrest, and apoptosis in rhabdoid tumour cell lines [45] and synovial sarcoma [41]. Overall, the data available in the literature regarding BRD9 function coupled with our data from Gene Ontology analysis further highlights the importance of studying this gene in the context of melanoma.…”
Section: Discussionmentioning
confidence: 67%
“…It is over-expressed in cervical cancer [12], promotes MYC expression and cell proliferation in acute myeloid leukemia [13]. Protein-engineering and inhibitor studies targeting BRD9 have shown promise in overcoming epigeneticallydefined drug resistance [14], and single or combinatorial effects of BRD9 inhibitors with doxorubicin or carboplatin also resulted in anti-proliferative effects in five malignant rhabdoid tumor cell lines [15]. Risdom et al revealed that epigenetic plasticity mediated by the chromatin modifier BRD4 drives survival of triple-negative breast cancer cells after targeted therapy treatment [16].…”
Section: Discussionmentioning
confidence: 99%